Insight: High intensity and activity carrier granular sludge cultured using polyvinyl alcohol/chitosan and polyvinyl alcohol/chitosan/iron gel beads. (April 2021) - Wang, Jinxing; Liang, Jidong
Graphical abstract: Highlights: The gel beads provides stable framework to guarantee cells entangling with EPS. Specific EPS components distribute in carrier granular sludge provides intensity. The interaction of Fe and protein promotes the intensity of carrier granular sludge. The porous gel beads supports mass transfer and benefits bacteria' metabolism. The environmental adaption of the microbes in carrier granular sludge are improved. Abstract: The newly developed carrier granular sludge (CGS) with polyvinyl alcohol/chitosan (PVA/CS) and PVA/CS/Fe gel beads assistance showed higher intensity and anammox activity than the natural granular sludge (NGS). Through comprehensive investigation, it was found: (1) the gel beads provided a stable framework of cells entangle with extracellular polymeric substances (EPS) to enhance the sludge intensity. In this framework, β-polysaccharides are distributed at the edge of CGS as a protection layer, α-polysaccharides and proteins are spread in the whole cross-section as backbones, and Fe 2+ /Fe 3+ in CGS-PVA/CS/Fe act as bridges to link with the negatively charged groups on bacterial surfaces and proteins. (2) The porous gel beads satisfied a relatively unimpeded mass transfer. Thus, the sludge activity, microbe's metabolism, membrane transportation and environmental adaption in CGS were apparently improved. The results improved the understanding about the advantages of the CGS and indicated their possible application in full-scale anammox processes.